MENGKAJI HUBUNGAN DI ANTARA KUALITI KEHIDUPAN DI KALANGAN PELAJAR TINGKATAN DUA DI SEKOLAH DENGAN PERATUS KEHADIRAN KE SEKOLAH - Nurhidaya, Ahmad (Universiti Malaysia Sarawak, UNIMAS, 2006)
Absenteeism in school always associated with the student’s variable such as self - concept and se lf - esteem, and family factor such as social economic status. However , school environment also leads to such phe nomenon therefore this study was conducted to identify the relationship between quality of school life and school attendance percentage. The respondents for this research were Form Two students of Sekolah Menengah Kebangsaan Green Road and Kolej Dato Patin ggi Abang Haji Abdillah where 140 respondents are involved. The instrument for this resea rch was a set of questionnaire Quality of School Life . Pearson Correlation indicated that there was no significant relationship between respondents’ feeling towards sc hool a nd school attendance percentage which meant that respondents’ feeling towards school did not influence school attendance percentage. Pearson Correlation also indicated that there was no significant relationship between respondents’ satisfaction towar ds school and school attendance percentage which meant that respondents’ satisfaction towards school did not influence school attendance percentage. Pearson Correlation also showed that there was significant relationship between respondents’ feeling toward s school and respondents’ satisfaction towards school. This showed that the higher the respondents’ feeling towards school, the higher the respondents’ satisfaction towards school. T - test indicated that there were no significant differences in respondents’ feeling towards school, respondents’ satisfaction towards school, and school attendance percentage based on gender factors. This showed that gender factors did not influence respondents’ feeling towards school, respondents’ satisfaction towards school, an d school attendance percentage. One - Way ANOVA showed that there were no significant differences in respondents’ feeling towards school, and respondents’ satisfaction towards school based on race factors. This showed that race factors did not influence resp ondents’ feeling towards school, and respondents’ satisfaction towards school. In contrast, One - Way ANOVA showed that there was significant difference in school attendance percentage based on their race. This showed that each race is different in school at tendance percentage. In conclusion, there was no correlation between quality of school life and school attendance percentage.